Comrades of color : East Germany in the Cold War world - Slobodian, Quinn 1978- Herausgeber (Protest, culture and society, 2015)
"This volume looks into the relationship that East Germany held with non-white socialistic nations, such as China and Cuba, as well as socialistic and communistic minorities in the United States. The volume also relates how these states and individuals saw East Germany"...Provided by publisher